2021
DOI: 10.3390/rs13214246
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Environmental Impacts of Vegetation Greening in a Semi-Arid Region of Northwest China since 2000

Abstract: The dynamics of terrestrial vegetation have changed a lot due to climate change and direct human interference. Monitoring these changes and understanding the mechanisms driving them are important for better understanding and projecting the Earth system. Here, we assessed the dynamics of vegetation in a semi-arid region of Northwest China for the years from 2000 to 2019 through satellite remote sensing using Vegetation Index (VI) data from the Moderate Resolution Imaging Spectroradiometer (MODIS), and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…However, several studies have demonstrated that grassland and semi-arid ecosystems contribute significantly to the increased global C sink in recent decades [16] , which is related to the greening trend in many dryland ecosystems that has been observed since the 1980s [11] . For example, in the semi-arid regions of China, land dominated by herbaceous plants has greened up much more than forests over the last 20 years [ 24 , 25 ]. In Australia, the prevalent La Niña conditions from 1981 to 2011 caused consecutive seasons with increased precipitation and thus vegetation cover expansion [17] .…”
Section: Biotic and Abiotic Processes Together Shape Grassland Carbon...mentioning
confidence: 99%
“…However, several studies have demonstrated that grassland and semi-arid ecosystems contribute significantly to the increased global C sink in recent decades [16] , which is related to the greening trend in many dryland ecosystems that has been observed since the 1980s [11] . For example, in the semi-arid regions of China, land dominated by herbaceous plants has greened up much more than forests over the last 20 years [ 24 , 25 ]. In Australia, the prevalent La Niña conditions from 1981 to 2011 caused consecutive seasons with increased precipitation and thus vegetation cover expansion [17] .…”
Section: Biotic and Abiotic Processes Together Shape Grassland Carbon...mentioning
confidence: 99%